Cancer chemotherapy and biotherapy : principles and practice - Chabner, Bruce; Longo, Dan L. (Dan Louis), 1949- (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Updated to include the newest drugs and those currently in development, Cancer Chemotherapy and Biotherapy, Fifth Edition is a comprehensive reference on the preclinical and clinical pharmacology of anticancer agents. Organized by drug class, the book provides the latest information on all drugs and biological agents--their mechanisms of action, interactions with other agents, toxicities, side effects, and mechanisms of resistance. Chapters emphasize pharmacology and mechanisms of action at the molecular and cellular levels, followed by clinical activity and toxicity, both acute and delayed. The authors explain the rationale for use of drugs in specific schedules and combinations and offer guidelines for dose adjustment in particular situations. The previous edition was one of "Doody's Core Titles 2009." This edition's introduction includes timely information on general strategies for drug usage, the science of drug discovery and development, economic and regulatory aspects of cancer drug development, and principles of pharmacokinetics. Eight new chapters have been added and more than twenty have been significantly revised"--Provided by publisher